2017
DOI: 10.1002/ejoc.201700072
|View full text |Cite
|
Sign up to set email alerts
|

Flow Dehydration and Hydrogenation of Allylic Alcohols: Application to the Waste‐Free Synthesis of Pristane

Abstract: Hydroxy‐substituted sulfonic acid functionalized silica (HO‐SAS) in combination with THF containing a small amount of water as a solvent proved to be a reliable system for the dehydration of allylic alcohols. This process generally caused dehydration within 1 min through a column reactor charged with HO‐SAS. The flow dehydration was sequenced by flow hydrogenation, which resulted in the synthesis of pristane. A scalable flow synthesis of pristane was successfully performed and afforded 10 g of pristane after a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…Then, we focused on silica-supported sulfonic acids (SAS) [ 7 , 8 ], for the flow dehydration step. Consequently, we found that the use of hydroxy-functionalized sulfonic acid silica, HO-SAS [ 9 , 10 , 11 ], for flow-dehydration worked well. Combined with the flow hydrogenation using Pd/C, we completed an acid waste-free flow synthesis of pristane ( Scheme 1 ) [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, we focused on silica-supported sulfonic acids (SAS) [ 7 , 8 ], for the flow dehydration step. Consequently, we found that the use of hydroxy-functionalized sulfonic acid silica, HO-SAS [ 9 , 10 , 11 ], for flow-dehydration worked well. Combined with the flow hydrogenation using Pd/C, we completed an acid waste-free flow synthesis of pristane ( Scheme 1 ) [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, we found that the use of hydroxy-functionalized sulfonic acid silica, HO-SAS [ 9 , 10 , 11 ], for flow-dehydration worked well. Combined with the flow hydrogenation using Pd/C, we completed an acid waste-free flow synthesis of pristane ( Scheme 1 ) [ 10 ]. Since Pd/C often causes dehydrative hydrogenation of allylic alcohols [ 12 , 13 , 14 , 15 , 16 , 17 ], we were curious as to whether pristane 3 could be synthesized using only a Pd/C catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…This catalyst is particularly useful in terms of thermal stability (up to 130°C) and enhanced acidity due to the β‐hydroxy substitution. Indeed, in our previous works using a flow‐setup based on a packed bed reactor containing HO‐SAS (Figure 1), we were able to conduct flow Fischer esterification reaction (Scheme 1, Equation 1) [ 7 ] and flow dehydration reaction of allylic alcohols (Scheme 1, Equation 2) [ 8,9 ] with a short period of residence time. Friedel–Crafts alkylation reaction starting with alcohols is a highly green process, [ 10,11 ] since water is the only byproduct as in the cases of Fischer esterification and dehydration of alcohols.…”
Section: Introductionmentioning
confidence: 99%
“…This led us to examine the reaction on a flow packed‐bed reactor using silica‐supported tertiary amine. Thus, the formed allene was introduced into a batch reactor containing C 60 (Scheme ) …”
Section: Resultsmentioning
confidence: 99%